Synthesis and Characterization of Heterogeneous Nano-Catalyst for the Production of Biodiesel from Pongamia Pinnata Oil - Aravindh N; Raja S; Rajasimman M; Vijayakumar B (Science & Technology Asia, 2025)
An alternate energy source for a variety of applications is provided by the production of biodiesel from Pongamia pinnata oil. To load MgO onto the ferrite-coated zirconium oxide, the impregnation method was used. A 0.5 mol solution of magnesium nitrate was allowed to dissolve in distilled water. After adding sodium hydroxide and CTAB, the mixture was added to a solution comprising ferrite- coated zirconium oxide and swirled constantly for eight hours at 65◦C using a hot plate magnetic stirring device. Once the color of the final solution changed, the introduction of sodium hydroxide was halted. The dense, viscous filtrate was cleaned using methanol and distilled water. After that, the thick sediment was dried by being kept at 110◦C for 12 hours in an oven. Lastly, the precursor material was calcined for three hours at 600◦C in a muffle furnace. To investigate its catalytic activity, the produced catalyst was evaluated using FTIR, SEM, XRD, and particle size analysis. A maximum yield of 97 wt% biodiesel was attained, when it was transesterified utilizing the ZrO2/MgO-Fe3O4 catalyst under different conditions: 6% (w/w) catalyst concentration, 15:1 methanol to oil molar ratio, 60◦C reaction temperature, and 240 min reaction duration. The ASTM standard was utilized for the analysis of the fuel qualities. It appears that the synthesized nanocatalyst is quite responsive in terms of both quality and effectiveness.